2018
DOI: 10.1021/acs.est.7b06476
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Relevant Concentrations of Carbamazepine Caused Endocrine-Disrupting Effects on Nontarget Organisms, Chinese Rare Minnows (Gobiocypris rarus)

Abstract: In the present study, Chinese rare minnows (Gobiocypris rarus) were exposed to 1, 10, and 100 μg/L of carbamazepine (CBZ) under flow-through conditions for 28 d. A hepatic-specific custom microarray identified 111 and 71 differentially expressed genes in the livers of females and males, respectively, exposed to 100 μg/L of CBZ (ratio ≥ 2, p ≤ 0.05). The levels of five differentially expressed genes associated with the hypothalamic-pituitary-gonadal (HPG) axis were quantified by qPCR, and the results indicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(9 citation statements)
references
References 58 publications
(104 reference statements)
1
7
0
Order By: Relevance
“…This result was similar to the behavior response based on behavior strength, suggesting that inhibition exerted by Cd can induce a decrease of swimming behavior, loss of coordination, and other kinds of behavior change of zebrafish [47]. Juhel et al observed that exposure to CBZ led to a significant reduction of AChE activity in Perna viridis [21]. Santos et al observed that exposure to 10 µg/L CBZ led to slight reduction of AChE activity in zebrafish [47].…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…This result was similar to the behavior response based on behavior strength, suggesting that inhibition exerted by Cd can induce a decrease of swimming behavior, loss of coordination, and other kinds of behavior change of zebrafish [47]. Juhel et al observed that exposure to CBZ led to a significant reduction of AChE activity in Perna viridis [21]. Santos et al observed that exposure to 10 µg/L CBZ led to slight reduction of AChE activity in zebrafish [47].…”
Section: Discussionsupporting
confidence: 60%
“…Oxidative stress has been reported as an important impact of CBZ on aquatic organisms [16][17][18]. Besides, CBZ was also found to cause delay in the first reproduction age in Daphnia magna [19], behavioral modification in Dugesia tigrina [20], and even endocrine-disrupting effects on Gobiocypris rarus [21].…”
Section: Introductionmentioning
confidence: 99%
“…As vertebrates, fish are perhaps more susceptible to pharmaceutical exposure than invertebrates because pharmaceuticals are designed for human (vertebrate) use. Data on the toxic effects of CBZ on fish have been reported for different species, such as the zebrafish (Danio rerio), Chinese rare minnows (Gobiocypris rarus), and Japanese medaka (Oryzia latipeus) [15][16][17][18][19][20]. For example, 0.5 µg/L CBZ exposure increased embryo mortality, lowered plasma steroid hormone levels, and decreased egg production in zebrafish [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most PPCPs in the environment have low concentrations, complex structures, and difficult degradation and accumulation characteristics [3]. Although the concentrations are low in the environment, long-term pollution of PPCPs may cause endocrine disruption or reproductive toxicity to aquatic organisms, induce changes in biochemical functions of aquatic habitats, and do great harm to the environment [4,5,6,7,8,9,10]. Carbamazepine (CBZ), a heavily used pharmaceutical, is mainly employed for the treatment of epilepsy, arrhythmia, depression, and other diseases [6].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of endocrine-disrupting effects, molting is used as an effective biomarker to assess the toxicity of contaminants in crustaceans. Previous studies have reported that various xenobiotics (such as polychlorinated biphenyls, perfluorooctane sulfonate, pesticides, and heavy metals) can affect molting in crustaceans by disrupting molting hormone signaling, including chitinolytic enzyme, 20-hydroxyecdysone, and molting hormone signaling genes [22,23,24,25,26]; however, as a neuro-active pharmaceutical, and a potential endocrine disruptor in fish [10], neither the effects of CBZ on molting in crustaceans nor the underlying mechanisms are well studied or understood.…”
Section: Introductionmentioning
confidence: 99%